Scoping Study On Economic Linkages And Options For Ecosystem Valuation Of Deep-Sea Living Marine Resources And Habitats In Abnj - FAO (Zenodo, 2017)
The second of a six-pieces collection of info-sheets about deep-sea sponges and their habitats, released by SponGES partner FAO.